Deterministic control of uncertain systems - Zinober, A. S. I. (Alan S. I.). (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1990)
The book reviews developments in the following fields: variable structure control; sliding mode control; hyperplane design; subspace attractivity; model-following control; canonical formulation; output feedback applications; hyperstability approach; nonlinear continuous feedback control; deterministic control; uncertain systems control; nonlinear composite control; continuous self-adaptive control and state observation.
Electronic reproduction.
Keywords: Automatic control; Control theory; Electronic books